Anthropometry and aquatic skills of children who attend swimming - Dias de Jesus, Eduarda Eugenia; Sperandio, Jessica; Faitarone Brasilino, Fabricio; Cortes Morales, Pedro Jorge (SPORT TK-EuroAmerican Journal of Sport Sciences, 2023)
The objective of this study is to analyze and compare anthropometric data and aquatic skills of children attending swimming lessons. 29 children participated, between 3 and 12 years old, enrolled in swimming classes. It was decided to determine the percentage of body fat (%BF) and the contents analyzed were: immersion, dorsal and ventral flotation, gliding and depth control. As for the BF% of the girls, all were at an "Optimal" level. However, it is possible to find boys generally classified in a health risk zone (p<0.02). A difference was observed in the results of aquatic skills, generating a positive score. It was concluded that according to the %BF of the boys, it is necessary to look for mechanisms to balance the %BF. When it comes to aquatic skills, the study shows that children are classified at a good level.